(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The study was carried out to assess the awareness of peoples on the impact of tannery waste disposal on environmental pollution of selected areas in Dhaka City. Data were collected by interviewing 300 peoples randomly of which 90 were labor, 60 livestock farmers, 60 fishermen and 90 were in local people in the study areas. Data were collected on age, education level, occupation, type of waste, color of waste, waste disposal time, environmental effect, human diseases, environmental pollution awareness, livestock diseases, livestock production and fisheries production. The findings revealed that about 34% respondents were illiterate. Both solid and liquid waste (56%) was come out from the tannery of which half of them were black in color. About 45% respondents were reported that the most environmental effect was bad smell to the surrounding areas. Survey result also showed different health problems such as skin diseases, itch, rash, cough, fever, diarrhea, headache, asthma, dizziness etc due to unplanned tannery waste disposal. The highest proportion (38%) of respondents had low environmental pollution awareness due to their education level. Livestock and poultry were died due to tannery waste indicated by 59% respondents. The livestock and fish production was low, reported by 48%. Education, occupation and type of waste had significant positive relationship where color of waste had no relationship with their environmental pollution awareness. The results of this study will be helpful to create peoples awareness on environmental pollution and their impact by tannery waste disposal. DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22164 J. Environ. Sci. & Natural Resources, 7(1): 149-156 2014